2020
DOI: 10.1126/science.aba9760
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics in postmitotic cells regulate neurogenesis

Abstract: The conversion of neural stem cells into neurons is associated with the remodeling of organelles, but whether and how this is causally linked to fate change is poorly understood. We examined and manipulated mitochondrial dynamics during mouse and human cortical neurogenesis. We reveal that shortly after cortical stem cells have divided, daughter cells destined to self-renew undergo mitochondrial fusion, whereas those that retain high levels of mitochondria fission become neurons. Increased mitochondria fission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(198 citation statements)
references
References 26 publications
8
188
1
1
Order By: Relevance
“…3E). The increase in Sox2 with Drp1 repression in the keratinocytes is consistent with findings in Drp1 ablated mouse embryonic fibroblasts (Parker et al, 2015) and neural stem cells (Iwata et al, 2020). Thus, unlike the stronger Drp1 knockdown, the weaker Drp1 knockdown maintains detectable Drp1 protein, and uniquely sustains a Sox2-hi/Krt15-hi population characteristic of the naturally Drp1 attenuated TF-1 population.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3E). The increase in Sox2 with Drp1 repression in the keratinocytes is consistent with findings in Drp1 ablated mouse embryonic fibroblasts (Parker et al, 2015) and neural stem cells (Iwata et al, 2020). Thus, unlike the stronger Drp1 knockdown, the weaker Drp1 knockdown maintains detectable Drp1 protein, and uniquely sustains a Sox2-hi/Krt15-hi population characteristic of the naturally Drp1 attenuated TF-1 population.…”
Section: Resultssupporting
confidence: 88%
“…Repression of Drp1 driven mitochondrial fission elevates stem/progenitor cell markers in mouse embryonic fibroblasts, and in cells of neural and ovarian epithelial lineage (Iwata et al, 2020, Parker et al, 2015). In the epidermal lineage, Krt15+ self- renewing stem cells contribute to both skin regeneration and carcinoma development (Giroux et al, 2017, Gonzales & Fuchs, 2017, Purba et al, 2014), while Sox2 upregulation in neoplastic stem/progenitor cells particularly supports skin carcinoma (Boumahdi et al, 2014, Siegle, Basin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The central role of mitochondria in neurogenesis is supported by numerous other reports that demonstrated the critical role of these organelles in regulating self-renewal and differentiation of NSCs during ontogeny and in the adult brain (Beckervordersandforth et al, 2017;Khacho et al, 2016Khacho et al, , 2019Khacho and Slack, 2018). A recent study by Iwata et al (2020) revealed that the fate dichotomy of differentiation/self-renewal during neurogenesis is resolved by instruction from mitochondria whereby reduction of mitochondrial activity by fusion is a major determinant of sustained self-renewal capacity. Our findings add a novel dimension to these reports by demonstrating that heme, a key component of mitochondrial ETC, is supplied from an unexpected source, that is, cannibalized erythroblasts, during brain development.…”
Section: Discussionmentioning
confidence: 77%
“…Activation of SIRT1 sensitizes neurons to oxidative stress [221,222] and inhibits neurogenesis [223] while RSV protects neurons against oxidative stress [224,225] and enhances neurogenesis [226,227]. Similarly, activation of SIRT1 promotes mitochondrial fission [228], and treatment with RSV rather enhances mitochondrial fusion [229]. Similarly, although brain-specific activation of SIRT1 drives anxiety and exploratory drive [48,230], RSV rather protects against autistic features [231][232][233][234].…”
Section: Rsv Is Also An Indirect Inhibitor Of Sirt1mentioning
confidence: 99%